CARBAPENEM-RESISTANT ENTEROBACTERIACEAE: NEW MENACE TO OUR ANTIBIOTIC ARMAMENTARIUM! - Porwal, Ankita; Bhat, Sevitha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: To study the risk factors, clinical characteristics, and outcome in patients with infections due to CRE infections. Methods: Retrospective study was carried out in a microbiology laboratory for 6 months. 152 CRE isolates identified by the Vitek 2 compact system were included in the study. The risk factors, antibiotic treatment and clinical outcome were studied from the case sheets, Chi-square test was used for statistical analysis. Results: Of the 2520 positive cultures for Enterobacteriaceae, isolation rate of CRE was 152 (6%). 76 (50%) belonged to exudates, 22 (14.1%) blood culture, 90 (59.2%) urine. The common infection was UTI. The risk factors were prior exposure to antimicrobials, admission to intensive care unit, indwelling devices and prior hospitalization. The effective antibiotic was colistin, polymyxin B, tigecycline, cefoperazone-sulbactum, piperacillin-tazobactum. The mortality was 19.7%. Conclusion: We have demonstrated the value of understanding local epidemiology to help modify our risk-based screening as a strategy to limit the spread of CRE.